Water, Sanitation and Hygiene Research in Humanitarian Crises: A Project Supporting the Child Health & Nutrition Research Initiative (CHNRI) Prioritization Exercise - Rohm, Elsa S. (Tufts Archival Research Center, 2022)
Water, sanitation, and hygiene (WASH) has a crucial role in responses to humanitarian emergencies which include natural disasters, conflicts, and disease outbreaks. Humanitarian emergencies are predicted to occur more frequently and affect larger numbers of people due to climate change. WASH interventions are used to disrupt the transmission routes of bacteria, viruses, and parasites that threaten human health. There is a need for the development of a consensus-based research agenda to guide the WASH in humanitarian crises field for the next ten years. This thesis supports a project developing this research agenda. Methods: Following the Child Health and Nutrition Research Initiative (CHNRI) methodology, research questions were developed through: a literature review; and, key informant interviews. In the literature review, research questions were first extracted from previous systematic reviews (2015, 2019), and then new searches were completed and research gaps extracted from recently published literature. Key informant interviews were conducted with stakeholders with expertise in the humanitarian WASH sector which included: NGO representatives, donors, government and ministry representatives, and university faculty, and then transcribed and research questions extracted. Informants were also asked questions to characterize the WASH research sector. Results: Overall, 404 research articles were reviewed and 23 key informant interviews were conducted. This resulted in a combined 934 research questions. After duplicates and questions not related to humanitarian emergencies were removed, 555 research questions remained. Questions were then cleaned, by merging and removing questions not WASH-relevant; 170 research questions remained, 62 from the literature and 108 from the key informant interviews. These questions represent every area of WASH interventions and generally look at effectiveness, health impacts, and sustainability. The characterization of the WASH research sector led to findings around the need to include different populations in the research process and improve the accessibility of research findings. Conclusions and Recommendations: While the CHNRI project is not yet completed, the research questions are being distributed to the sector for scoring. This project led to the development of 170 total research questions. This will allow for the development of a prioritized research agenda for the WASH sector for the next ten years.; Thesis (B.S.E.V.E.)--Tufts University, 2022.; Submitted to the Dept. of Civil and Environmental Engineering.; Keywords: WASH research agenda, Humanitarian crises.